Institutional Arrangement on Welfare Regime in Indonesia: How Does Indonesia Maintain Its Health Care Policy - Pradhikna Yunik Nurhayati (Jurnal Empirika, 2020)
In the last decade, Indonesia has successfully reduced the poverty rate from 11.96% in 2012 to 9.22% at the end of 2020. However, the rate of inequality in Indonesia is considered the highest within the region. Therefore, it is pivotal for Indonesia to strengthen and expand its welfare system in order to overcome the inequality. This paper aims to examine the institutional arrangement of welfare regime in Indonesia especially the health care policy. This paper implement qualitative method by examine secondary resource such as journals, articles and government report to gain understanding about institutional arrangement on welfare system in Indonesia. Result shows that population coverage of health care is shifting gradually from partial group of population to all of the citizens especially by the existence of national health insurance. The source of funding is risk-pooling rather than self-help. It indicates that government of Indonesia embrace inclusive productivist welfare as its institutional arrangement.